2013
DOI: 10.1097/igc.0b013e3182842fc4
|View full text |Cite
|
Sign up to set email alerts
|

Does Extensive Upper Abdomen Surgery During Primary Cytoreduction Impact on Long-term Quality of Life?

Abstract: Upper abdomen surgery is a feasible and safe therapeutic option. Patients present same times of beginning of chemotherapy without an increase in chemorelated toxicities and experience the same general quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…One study with 89 patients did attempt to compare PRO after standard and extensive surgery, but the questionnaires were only taken at the first follow-up appointment after completion of all treatments, lacking information on trend of PRO across a certain time frame. 23 The study reported no statistical differences in major surgical complication rates (15% vs 10%) and no severe chemotherapy-related toxicities. Patientreported outcome scores were comparable in both groups.…”
Section: Discussionmentioning
confidence: 79%
“…One study with 89 patients did attempt to compare PRO after standard and extensive surgery, but the questionnaires were only taken at the first follow-up appointment after completion of all treatments, lacking information on trend of PRO across a certain time frame. 23 The study reported no statistical differences in major surgical complication rates (15% vs 10%) and no severe chemotherapy-related toxicities. Patientreported outcome scores were comparable in both groups.…”
Section: Discussionmentioning
confidence: 79%
“…Our methodologically robust multicentre study confirms findings from smaller single‐centre studies. 24 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Our methodologically robust multicentre study confirms findings from smaller single-centre studies. 24,43 Those undergoing high-SCS procedures had significantly greater disease burden and more upper abdominal disease, but patients with these disease characteristics also underwent surgery of low or intermediate complexity. As some women with comparably high disease burden would not have been offered surgery, understanding the QoL and survival of these patients not undergoing surgery is essential if the true value or detriment from high-SCS surgery is to be assessed.…”
Section: Main Findingsmentioning
confidence: 99%
“…If on one hand complex surgery for ovarian cancer has increased direct medical costs, it appears to have provided good value for money spent [11] without compromising long-term quality of life [12]. However, the upper abdominal surgical procedures have made it necessary to know and manage related complications [6].…”
Section: Discussionmentioning
confidence: 99%